Bis(pinacoloto)diboron/4-Phenylpyridine System for One-Pot Photocatalyzed Borylation and Reduction of Aldehyde: Synthesis of Tavaborole in a Flow Reactor - Kumar, Kankanala Naveen; Mhate, Mouzma; Ravichandiran, Velayutham; Swain, Sharada Prasanna (Synthesis, 2023)
A photocatalyzed one-pot borylation of haloarene and reduction of aldehyde by cocatalysis of bis(pinacoloto)diboron/4-phenylpyridine is reported. The reaction was carried out in a flow reactor by irradiating the reaction at 410 nm, with residence time of 10 minutes. The method was successfully applied for the synthesis of tavaborole in a single step with 81% yield.
Keywords: tavaborole; photocatalysis; flow chemistry; green chemistry; one-pot synthesis